2017
DOI: 10.3390/metabo7030033
|View full text |Cite
|
Sign up to set email alerts
|

NMR Profiling of Metabolites in Larval and Juvenile Blue Mussels (Mytilus edulis) under Ambient and Low Salinity Conditions

Abstract: Blue mussels (Mytilus edulis) are ecologically and economically important marine invertebrates whose populations are at risk from climate change-associated variation in their environment, such as decreased coastal salinity. Blue mussels are osmoconfomers and use components of the metabolome (free amino acids) to help maintain osmotic balance and cellular function during low salinity exposure. However, little is known about the capacity of blue mussels during the planktonic larval stages to regulate metabolites… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…Our results further indicated that the contents of glutamate, glycine, alanine, and/or aspartate were also downregulated upon low‐salinity challenge, which is consistent with the findings in other bivalves when transferred to lower salinities. For example, the downregulated contents of alanine and glycine have been reported in the gill and mantle of juvenile blue mussel ( Mytilus edulis ) when transferred from 32‰ to 20‰ SW (May et al, 2017). In addition, the contents of other FAAs, such as glutamate, glycine, alanine, and aspartate, have also been observed to be downregulated in the mantle of the Pacific oyster after transfer to 50% seawater (Hosoi et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Our results further indicated that the contents of glutamate, glycine, alanine, and/or aspartate were also downregulated upon low‐salinity challenge, which is consistent with the findings in other bivalves when transferred to lower salinities. For example, the downregulated contents of alanine and glycine have been reported in the gill and mantle of juvenile blue mussel ( Mytilus edulis ) when transferred from 32‰ to 20‰ SW (May et al, 2017). In addition, the contents of other FAAs, such as glutamate, glycine, alanine, and aspartate, have also been observed to be downregulated in the mantle of the Pacific oyster after transfer to 50% seawater (Hosoi et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, in terrestrial and limnic systems, researchers used exometabolomics to study soil organic matter cycling (6, 7), overflow metabolism of cultivable microorganisms (8, 9), and chemical ecology of the environment (10, 11). While intracellular metabolomic analyses of tissues from marine microbial cells to invertebrates are becoming increasingly more common (1214), the defining characteristic of marine habitats, i.e., high salt concentration, limits exometabolomic analyses of the oceans to studies that require salt removal prior to metabolite extraction (10, 15, 16).…”
Section: Introductionmentioning
confidence: 99%
“…Osmoconformers are organisms that maintain an osmotic pressure equivalent to that of the external environment using organic osmolytes like taurine, betaine, and homarine (Yancey 2005). These osmolytes have been detected in several marine invertebrates such as polychaetes ( Glycera ), snails ( Mitrella carinata ; Yancey 2005), mussels ( Mytilus edulis ; Tuffnail et al 2009; May et al 2017), and jellyfish (Boco et al 2019; Stabili et al 2019). These specific osmolytes were indeed present at relatively high abundances in jellyfish polyps, but no differences were observed due to pesticide exposure in the present study.…”
Section: Discussionmentioning
confidence: 99%